VDAC1: from structure to cancer therapy - Shoshan-Barmatz, Varda; Mizrachi, Dario (Frontiers in Oncology, 2012)
Here, we review current evidence pointing to the function of VDAC1 in cell life and death, and highlight these functions in relation to cancer. Found at the outer mitochondrial membrane, VDAC1 assumes a crucial position in the cell, controlling the metabolic cross-talk between mitochondria and the rest of the cell. Moreover, its location at the boundary between the mitochondria and the cytosol enables VDAC1 to interact with proteins that mediate and regulate the integration of mitochondrial functions with other cellular activities. As a metabolite transporter, VDAC1 contributes to the metabolic phenotype of cancer cells. This is reflected by VDAC1 over-expression in many cancer types, and by inhibition of tumor development upon silencing VDAC1 expression. Along with regulating cellular energy production and metabolism, VDAC1 is also a key protein in mitochondria-mediated apoptosis, participating in the release of apoptotic proteins and interacting with anti-apoptotic proteins. The involvement of VDAC1 in the release of apoptotic proteins located in the inter-membranal space is discussed, as is VDAC1 oligomerization as an important step in apoptosis induction. VDAC also serves as an anchor point for mitochondria-interacting proteins, some of which are also highly expressed in many cancers, such as hexokinase (HK), Bcl2, and Bcl-xL. By binding to VDAC, HK provides both metabolic benefit and apoptosis-suppressive capacity that offers the cell a proliferative advantage and increases its resistance to chemotherapy. VDAC1-based peptides that bind specifically to HK, Bcl2 or Bcl-xL abolished the cell’s abilities to bypass the apoptotic pathway. Moreover, these peptides promote cell death in a panel of genetically characterized cell lines derived from different human cancers. These and other functions point to VDAC1 as a rational target for the development of a new generation of therapeutics.